Efektivitas Pemanfaatan Media Facebook pada Laman Notifikasi Beranda untuk Meningkatkan Kemampuan Menulis Puisi Siswa Kelas X SMA Nurul Iman: Efektivitas Dalam Pemanfaatan Media Facebook - Fadhilla Pratiwi; Dra. Rosmawati Harahap.,M.Pd.,Ph.D. (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The research was carried out which aims to describe the use, application, and use of facebook media on the notification page of the homepage in writing poetry by students of class X SMA Nurul Iman. This study uses a quantitative descriptive method with a population of 180 people and a set sample of 27 people. The total sample is 15% of the total population. The highest score obtained is 90 while the lowest score is 75. Based on the results of data analysis, the average utilization, application, and use of facebook media on the notification page homepage by class X SMA Nurul Iman students is 81.85 (85%) which is categorized as "good" . The ability to use the Facebook home page by class X SMA Nurul Iman tests based on a poetry writing test on Facebook media on the home page notification is equal to 69.00 which is included in the "fairly capable" category. This is evidenced by the results of the poetry writing test on Facebook media on the home notification page showing his ability with an average score of 81.85 (good). The calculation of the score for writing poetry on Facebook media on the homepage notification page for class X students of SMA Nurul Iman in the 2021-2022 academic year is the same as 81.85. The average score of class X students at SMA Nurul Imanfor the academic year 2021-2022 is the same as 81.85 which is qualified into the category B (Good).